Impact of Diabetes Mellitus on Drug-Induced Liver Injury during Antituberculosis Therapy: A Prospective Cohort Study - Ruina Chen; Yu Wu; Xiaoyan Xu; Jingru Cheng; Yan Jiang; Xiaomin He; Hongqiu Pan; Meiling Zhang; Lihuan Lu; Honggang Yi; Shaowen Tang (The American Journal of Tropical Medicine and Hygiene, 2026)
ABSTRACT. Drug-induced liver injury (DILI) is a significant concern during antituberculosis (anti-TB) treatment, and its association with diabetes mellitus (DM) remains inconsistent. This study investigated whether DM influences anti-TB DILI occurrence in Chinese patients. A prospective cohort study enrolled patients receiving anti-TB treatment at four hospitals. Patients were grouped by DM status and followed up until treatment completion. Propensity score matching (PSM) was performed at a 1:1 ratio to ensure comparability. Multivariate Cox regression analysis was used to identify risk factors for DILI. Among 3,952 TB patients (759 with DM), 522 developed DILI. No significant difference was observed in the incidence of DILI between DM and non-DM patients (14.6% versus 12.9%, P = 0.333), and Kaplan–Meier analysis yielded similar results ( P = 0.317). After PSM, 350 cases were included in each group. Glycated hemoglobin data were available for 122 DM and 64 non-DM patients, with median levels of 7.8% and 5.5% at diagnosis and 7.1% and 5.5% at the end of therapy, respectively. Multivariate analysis showed that DM comorbidity did not increase DILI risk (hazard ratio [HR] = 0.921, 95% CI = 0.705–1.202, P = 0.544). Preventive use of hepatoprotective drugs significantly reduced DILI risk (HR = 0.622, 95% CI = 0.470–0.823, P